Determination of Iodate and Iodide Content in Iodized Salt By Ion Pair High Performance Liquid Chromatography Method - Wisnu Cahyadi; Kurnia Firman; Slamet Ibrahim; Embit Kartadarma (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
Two species of iodine, i.e. iodide and iodate in commercial iodized salt were determined using ion pair HPLC. From 15 samples analysed, the iodide and iodate content ranged from 24,05 ± 2,51 to 70,25 ± 3,78 ppm and from 31,43 ± 8,10 to 87,59 ± 0,44 ppm, respectively. The method used was found satisfactory in terms of precission, accuracy, sensitivity and selectivity, therefore the method seem acceptable for the determination of iodide and iodate content in iodized salt samples. Key words : Iodine species, determination of iodine species content, and ion-pair HPLC